The effects of acute interval cycling and blood flow restriction on hematologic factors of beginner cyclists - Hadi Bashafaat; Mohammad Ismail Afzalpour; Ali Asghar Fallahı; Saeed Nazıfı; Said Ilbeıgı (Türk Spor ve Egzersiz Dergisi)
Blood compositions change as a result of physical activity and an exercise associated with Blood Flow Restriction (BFR) is a new exercise method. This study aims to compare the acute effect of an interval exercise with blood flow restriction on beginner cyclists’ hematologic factors.  Twenty students of Shiraz Education Cycling Team with an age average of 16.43 ± 1.36 years, weight of 60.07 ± 11.74 kg and height of 175.46 ± 6.14 cm participated voluntarily in this experimental study. The participants were divided randomly into two equal groups of interval cycling with BFR (n=10) and interval cycling without BFR (n=10). Interval exercise consisted of 10 repetitions for one minute and one-minute rest between repetitions. BFR was applied by cuff with a width of 15 cm and pressure of 160 mmHg. Before and immediately after the exercise, 5 ml blood sample was taken from a brachial vein. The results were extracted using dependent and independent T-test statistical methods at the significance level of P lt;0.05 by SPSS 23. The results showed the increasing effect of acute interval cycling with BFR on White Blood Cells (WBC), Red Blood Cells (RBC), Hemoglobin (Hb), Hematocrit (Hct) and Platelets (PLT) as well as the increasing effect of acute interval cycling without BFR on WBC and PLT. No significant difference was observed between the effects of the two exercise methods on hematologic factors (P lt;0.05). Acute interval cycling with BFR increased five hematologic indexes; however, acute interval cycling without BFR increased two hematologic indexes. It seems that interval exercise with BFR makes wide hematologic changes among beginner cyclists.